(untitled) (Research, Society and Development, 2025)
Conduct Disorder is a complex psychiatric disorder that significantly impacts the lives of individuals, their families, and the broader community. The purpose of this paper is to present a detailed presentation of conduct disorder, with a particular focus on the social and environmental dimensions of the phenomenon. Special attention is given to comorbidity and interventions that can be applied in various settings, such as the family, school, and community. Furthermore, integrating sociological perspectives is highlighted, emphasizing the relationship between the disorder and social factors such as family dynamics, educational environments, and social inequalities. Strategies for early intervention, school-based programs, and therapeutic approaches are discussed as essential in addressing the disorder effectively. The paper underscores the significance of collaborative efforts among mental health professionals, educators, and families to foster social cohesion and enhance mental health outcomes. By framing Conduct Disorder as a multidimensional and sociocultural phenomenon, this study contributes to a deeper understanding of its implications and developing comprehensive treatment strategies.